Efektivitas Otago Exercise Program terhadap Keseimbangan Lansia - Setiani, Ribka; Wahyu W, Afrianti; Fithriati H, Nurul (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: As individuals aged, they experienced a decline and morphological changes in the neuromuscular system, which led to functional changes. A common health problem among the elderly was impaired physical function, characterized by a decrease in body balance. One of the efforts that could be made to improve body balance, lower limb muscle strength, and the vestibular system was through the Otago Exercise Program. Objectives: This study aims to determine and analyze the effect of giving otago exercise program in improving balance in the elderly. Methods: This study used a quantitative approach through the type of Quasi-Experimental research with the method of one group pre and post-test with control group design. The treatment group was given the otago exercise program and education and the control group was given education. Sampling using purposive sampling method Results: The results of statistical tests using paired sample t-test obtained results p = <0.001 (<0.05) means that there is an effect of giving otago exercise program on the balance of the elderly. Conclusion: Otago exercise program can improve balance in the elderly. Keywords : Otago Exercise Program, Balance, Elderly